2019
DOI: 10.1155/2019/5261830
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Spectral PRP Conjugate Gradient Projection Method for Solving Large‐Scale Monotone Equations and Its Application in Compressed Sensing

Abstract: In this paper, we develop an algorithm to solve nonlinear system of monotone equations, which is a combination of a modified spectral PRP (Polak-Ribière-Polyak) conjugate gradient method and a projection method. The search direction in this algorithm is proved to be sufficiently descent for any line search rule. A line search strategy in the literature is modified such that a better step length is more easily obtained without the difficulty of choosing an appropriate weight in the original one. Global converge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Esmaeili, et al (2018) suggested a new CG scheme to solve problems emerged from astronomical imaging, file restoration, image video coding and other applications. Similarly, Guo & Wan (2019) developed CG algorithm for sparse engineering signal problem. Numerical tests indicated that the algorithm is an alternative for recovering sparse signal problems and beats earlier methods.…”
Section: Extended Conjugacy Condition Of Dai and Liao Cg Methods (Eccdl)mentioning
confidence: 99%
“…Esmaeili, et al (2018) suggested a new CG scheme to solve problems emerged from astronomical imaging, file restoration, image video coding and other applications. Similarly, Guo & Wan (2019) developed CG algorithm for sparse engineering signal problem. Numerical tests indicated that the algorithm is an alternative for recovering sparse signal problems and beats earlier methods.…”
Section: Extended Conjugacy Condition Of Dai and Liao Cg Methods (Eccdl)mentioning
confidence: 99%
“…Recently, an adaptive line search approach that takes into consideration a disturbance component was presented by Liu et al [33] and Guo and Wan [34], i.e., the step size α k � max aρ i : i � 0, 1, . .…”
Section: 􏼈 􏼉 Such Thatmentioning
confidence: 99%
“…Since a nonlinear system of equations is closely related with an optimization model, it is significant to extend the developed algorithm into solving large scale nonlinear system of equations from engineering fields. Actually, it has been shown [20], [22] that recovering sparse signals and restoring blurred images can be formulated as a system of equations, and efficient optimization algorithms can be modified to solve these practical engineering problems.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…One of our goals in this paper is to find a better scaling parameter such that the corresponding algorithm is more efficient and robust. For many large-scale practical optimization models [22], [23], the (scaling) BFGS algorithms like (3) and ( 4) are often powerless because they are associated with solution of a large-scale system of linear equations B k d k = −g k , as well as computation and storage of matrices B k with large sizes. Therefore, another goal in this paper is to modify the scaling BFGS algorithms such that only gradient information in the optimization problem (1) is employed to compute the search directions and the step sizes without needs of computing and storing matrices [15].…”
Section: Introductionmentioning
confidence: 99%